Analisis Digital Divide Terhadap Penggunaan Mobile Banking Di Kota Purwokerto - Dinda Varas Sagita; Refi Rifaldi Windya Giri (STIE AMKOP, 2023)
Technological developments in the era of the digital economy (Industrial Revolution 4.0) are unavoidable, one of the uses that is currently developing a lot is the digital payment system which is growing rapidly. The banking industry is one of the industries that participates in taking advantage of technological developments where banks innovate to develop companies. This is realized by the banking sector by developing a service system for customers in the form of mobile banking. However, it is necessary to know clearly whether the use of mobile banking in Indonesia is evenly distributed in every province, for this reason this research is aimed at finding out whether there is a digital gap in the use of mobile banking applications, especially in Purwokerto City. This study aims to find out whether the digital divide which has four stages which become variables in this study, namely motivation, physical and material access, mobile banking skills, and usage influence each other. In addition, it is also to find out whether the moderating variables, namely gender, age, and education each have an influence on the relationship between these variables. The method used in this research is using quantitative methods and using PLS-SEM analysis. The number of respondents in this study amounted to 305 respondents who were obtained through distributing questionnaires. The sampling technique was carried out using non-probability sampling with purposive sampling method. Data is processed using WarpPLS 7.0 software. The results of this study indicate that the variables motivation, physical and material access, mobile banking skills, and usage are significant. Which means there is no digital divide in the use of mobile banking. And these four variables affect the use of mobile banking. This research is used to assist the banking industry in evaluating its business, especially in digital banking. Apart from that, the government still needs to carry out more comprehensive digital literacy for Indonesian people, especially in rural areas. Keywords: Digital divide, Mobile banking, Consumer Behavior.